The Influence of Employee Competence and Work Culture on Service Quality: The Moderating Role of Information Technology in the One-Stop Integrated Service at the East Jakarta BPN Office - Theresia Riyanti (Journal AGENCY, 2025)
This study investigates the influence of employee competence and work culture on service quality, with information technology examined as a moderating variable in this relationship. In the context of the One-Stop Integrated Service (PTSP) at the East Jakarta BPN Office, the research highlights how internal organizational factors and technological support contribute to improving public service outcomes. A quantitative research design was employed, utilizing a moderated regression analysis approach. Data were gathered through structured questionnaires distributed to employees and were analyzed using SPSS software. The findings reveal that employee competence and work culture have a positive and significant impact on service quality. Additionally, information technology also shows a direct positive influence on service quality. The interaction effects between employee competence and information technology, as well as between work culture and information technology, are both statistically significant. These results confirm that information technology acts as a strengthening factor in the relationship between the independent variables and service quality. The study underscores the strategic role of human capital development and cultural reinforcement, along with digital transformation, in enhancing the performance of public service institutions. The implications suggest that policymakers and organizational leaders should invest in continuous employee training, cultivate a constructive work environment, and adopt integrated information systems to meet increasing public expectations and deliver high-quality services.